2012
DOI: 10.1371/journal.pone.0044450
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Monocytes but Not TIE2-Expressing Monocytes Are a Sensitive Diagnostic Indicator for Colorectal Cancer

Abstract: We have conducted the first study to determine the diagnostic potential of the CD14++CD16+ intermediate monocytes as compared to the pro-angiogenic subset of CD14++CD16+TIE2+ TIE2-expressing monocytes (TEMs) in cancer. These monocyte populations were investigated by flow cytometry in healthy volunteers (N = 32) and in colorectal carcinoma patients with localized (N = 24) or metastatic (N = 37) disease. We further determined blood levels of cytokines associated with monocyte regulation. The results revealed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 42 publications
2
33
1
3
Order By: Relevance
“…11,12 Importantly, there were no significant differences in the gene expression profiles between monocyte subsets isolated from healthy controls and mCRC patients, even though we have previously shown that the frequency of subpopulations differs significantly between healthy individuals and mCRC patients. 16 Furthermore, chemotherapy did not alter the gene expression profile of monocyte subsets in mCRC patients. We therefore conclude that the presence (and therapy) of a tumor affects the frequency of monocyte subsets without changing their functional phenotype or identity in terms of characteristic transcript pattern.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…11,12 Importantly, there were no significant differences in the gene expression profiles between monocyte subsets isolated from healthy controls and mCRC patients, even though we have previously shown that the frequency of subpopulations differs significantly between healthy individuals and mCRC patients. 16 Furthermore, chemotherapy did not alter the gene expression profile of monocyte subsets in mCRC patients. We therefore conclude that the presence (and therapy) of a tumor affects the frequency of monocyte subsets without changing their functional phenotype or identity in terms of characteristic transcript pattern.…”
Section: Discussionmentioning
confidence: 91%
“…In line, when we previously compared TEM frequency in the blood of CRC patients and healthy individuals, no significant difference was detected. 16 While this finding may be specific to the respective tumor entity, 27 it might also relate to the lower frequency of TEMs (as compared to intermediate monocytes) and hence detection limit in circulation. Since it was previously demonstrated in mouse models that pro-angiogenic, myeloid cell populations could confer resistance to anti-VEGF cancer therapy by providing substitute growth factors, 28,29 it was feasible to hypothesize that bevacizumab treatment might alter TEM frequency to compensate for the loss in VEGF activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations